2023
DOI: 10.3389/fendo.2023.1061235
|View full text |Cite
|
Sign up to set email alerts
|

Progress in salivary glands: Endocrine glands with immune functions

Abstract: The production and secretion of saliva is an essential function of the salivary glands. Saliva is a complicated liquid with different functions, including moistening, digestion, mineralization, lubrication, and mucosal protection. This review focuses on the mechanism and neural regulation of salivary secretion, and saliva is secreted in response to various stimuli, including odor, taste, vision, and mastication. The chemical and physical properties of saliva change dynamically during physiological and pathophy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 152 publications
0
11
0
Order By: Relevance
“…Furthermore, although it is documented that a chronic sialocele can theoretically become secondarily infected (13), subjectively infection is clinically rare and to the authors'knowledge has never been reported in the literature. The dearth of infected sialocele reports may be due to the antimicrobial and immune properties of saliva (32)(33)(34). Salivary glands have resident B cells, T cells, macrophages, and dendritic cells, enabling them to be an integral part of both the innate and adaptive immune response (32,33) in the oral cavity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, although it is documented that a chronic sialocele can theoretically become secondarily infected (13), subjectively infection is clinically rare and to the authors'knowledge has never been reported in the literature. The dearth of infected sialocele reports may be due to the antimicrobial and immune properties of saliva (32)(33)(34). Salivary glands have resident B cells, T cells, macrophages, and dendritic cells, enabling them to be an integral part of both the innate and adaptive immune response (32,33) in the oral cavity.…”
Section: Discussionmentioning
confidence: 99%
“…The dearth of infected sialocele reports may be due to the antimicrobial and immune properties of saliva (32)(33)(34). Salivary glands have resident B cells, T cells, macrophages, and dendritic cells, enabling them to be an integral part of both the innate and adaptive immune response (32,33) in the oral cavity. Furthermore, salivary peroxidases, most notably lactoperoxidase, can generate hypothiocyanous acid, which has direct oxidative antimicrobial effects (34).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, this may reflect the presence/activation of steroidogenic enzymes, or sulfatase enzyme, which converts the sulfated form of DHEA (DHEAS) into DHEA ( 14 ). Conversely, despite saliva flow rate varies during the day and it is affected by stimuli related to feeding ( 35 ), the salivary concentration of HC and other unconjugated steroids is not affected by saliva flow rates, and it is the result of passive diffusion of free steroids, HC in particular, across the acinar cells of the salivary gland ( 12 ).…”
Section: Discussionmentioning
confidence: 99%
“…Salivary glands have wide range of functions. For example, salivary glands play a pivotal role in immunity, endocrine and salivary secretion 13) . Furthermore, salivary glands condition contributes to the overall quality of life 14) .…”
Section: Two-generation Exposure To a High-fat Diet Alters Duct Cell ...mentioning
confidence: 99%